Enforcement of the Advocate Code of Ethics Against Legal Misconduct by Advocates: A Perspective of Amanah and Justice Principles in Islamic Law - Dimas Abdurochim; Ummu Aisyah; Tamimatun Nihayah; Musleh Harry (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Advocates occupy a strategic position as law enforcers and play a crucial role in ensuring access to justice, protecting legal rights, and maintaining the integrity of judicial processes. However, the increasing involvement of advocates in legal misconduct, including bribery, corruption, document forgery, breaches of confidentiality, conflicts of interest, and obstruction of justice, has raised serious concerns regarding professional integrity and ethical accountability. This study aims to analyze the enforcement of the Advocate Code of Ethics against advocates who commit legal misconduct and to evaluate such enforcement through the principles of amanah (trustworthiness) and al-‘adl (justice) in Islamic law. This study employed normative legal research using statutory, conceptual, and Islamic law approaches. The research relied on primary, secondary, and tertiary legal materials collected through an extensive literature review and analyzed using qualitative legal analysis. The findings reveal that although ethical enforcement in Indonesia is supported by a relatively comprehensive legal framework through Law Number 18 of 2003 and the Indonesian Advocate Code of Ethics, its implementation remains constrained by weak disciplinary supervision, inconsistent sanctions, limited transparency, institutional fragmentation among advocate organizations, and the separation between ethical accountability and criminal liability. From the perspective of Islamic law, legal misconduct committed by advocates reflects a failure to uphold the principles of amanah and justice, which constitute the moral foundation of professional integrity. This study offers an integrative analytical framework that combines positive law and Islamic legal ethics to evaluate ethical enforcement and argues that strengthening advocate professionalism requires not only regulatory compliance but also the internalization of trustworthiness, fairness, accountability, and justice.